A qualitative study on 6th year medical students' perceptions of and self-reported competence in clinical practice after receiving resuscitation-based simulation training - Jansen, Marvin Jeffrey (Division of Emergency Medicine, 2016)
Background: Despite practicing resuscitation skills in a simulation environment, medical students often express anxiety about having to participate in patient resuscitation in the clinical environment. This fear can lead to an unwillingness to initiate or participate in resuscitations, and a decreased confidence in their skills. Exploring the perceptions of final year medical students can provide valuable insight for improving the current simulation programme at the University of Cape Town. Aim: The aim of the study is to explore 6th year medical students' perceptions and self-reported competence for clinical practice after receiving Resuscitation-Based Simulation training.